TOKOH PENDUKUNG SEBAGAI TANDA PENGUAT PESAN PADA FILM TALAK 3 - Sri Rahayu Ramadhani; Titus Soepono Adji (TEXTURE : Art and Culture Journal, 2018)
Supporting actors and supporting actresses in films have an important influence on the course of the story. Their presence is able to strengthen the messages conveyed through scenes in the film. The formulation of the problem of this research is how to read the supporting cast as a message reinforcement on the film Talak 3. Film Talak 3 by Hanung Bramantyo and Ismail Basbeth tells the story of the desire of a divorced couple to reconcile. The supporting figures in the film Talak 3 were used as the focus of the study. The study was conducted using a type of qualitative descriptive research, while the approach method applied the semiotic theory of Roland Barthes to analyze the supporting characters who had the role of signaling the message in the scene. The results of this study show that the budhe Ratna as a supporting actress strengthens the message using marriage life and the meaning of true love that appears throughout the film. Messages related to bureaucracy in government agencies are strengthened by the presence of figures Basuki, Hasmi, Jonur and Ical.Keywords: message, supporting actor and actress, Roland Barthes’s semiotics, Film Talak 3